PEMBERIAN DOLOMIT DAN KALIUM UNTUK PENINGKATAN LAJU PENGISIAN FOTOSINTAT PADA UMBI TANAMAN UBI JALAR (Ipomoea batatas L.) - Bondan Hary Setiawan; Arum Asriyanti Suhastyo (Jurnal Ilmiah Media Agrosains, 2016)
Study the importance of the effect of the addition of dolomite and potash fertilizer in an advanced stage based on the research that has been done and their interactions to increase the production of sweet potato. Research should be conducted during the months of September to December 2014 at the Polytechnic Experiment Land Banjarnegara. Materials used include : sweet potato seedlings, dolomite, KCl. Tools used include : a hoe, scales. The observed variables include : K is available, exchangeable Aluminium, tubers volume (cm3), weight of tuber per plant (kg), weight of tuber per hectare (kg), sugar content in the tubers. The experimental design used was a draft Plots Divided (split plot design) where there are two factors and each factor there are 2 treatment, namely : factor dolomite (D) include treatment : without the addition of dolomite (D0) and the addition of dolomite 5 ton/ha (D1). Factor the addition of potassium (K) include treatment : without the addition of potassium (K1), the addition of potassium up to 225 kg/ha (K2), the addition of potassium up to 300 kg/ha (K2), the addition of potassium up to 375 kg/ha (K3). Analysis of data using ANOVA test with a confidence level of 95%, followed by a further test DMRT. The results showed award specifies the treatment of dolomite no significant increase the weight of tubers per plant, weight of tuber per hectare and the volume of tubers per plant. Giving potassium treatment gives a noticeable difference to the volume parameter of tubers per plant. Interaction dolomite and potassium provide real difference in carbohydrate content in the delivery of 5 tons per hectare dolomite and potassium of 300 kg/hectare.